Effect of Breadfruit Leaf Powder (Artocarpus altilis) on Performance, Fat and Meat Cholesterol Level and Body Immune of Male Native Tegal Duck - Tugiyanti , Elly; Setianto, Novie Andri; Harisulistyawan, Ibnu; Susanti, Emmy; Mastuti, Sri (International Journal of Poultry Science, 2016)
This research was aimed to investigate the effect of the breadfruit leaf powder on performance, fat and meat cholesterol level and body immune of male Tegal duck. Completely Randomized Design with six treatments includes b0: feed without breadfruit leaf powder, b1: feed + 3%/kg feed breadfruit leaf powder, b2: feed + 6%/kg feed breadfruit leaf powder b3: feed + 9%/kg feed breadfruit leaves powder, b4: feed + 12%/kg feed breadfruit leaves powder, b5: feed + 15%/kg feed breadfruit leaves powder had applied in this study. Each treatment had 5 replicates with 4 ducks, comprising 120 male Tegal ducks in total. Treatments were given for 5 weeks from one month old to slaughter age of 9 weeks old. Data were subject to analysis of variance and should differ be observed across treatments, Honestly Significant Difference test ensued. Analysis of variance showed that supplementation of breadfruit leaf powder did not significantly affect (p>0.05) on body weight, feed conversion and carcass percentage of 9-week old male Tegal duck, but significantly affected (p<0.05) fat level, meat cholesterol, total of protein plasma, hemoglobin level and ratio of H/L. Conclusively, breadfruit leaf powder had a strong antioxidant activity and was safe for male Tegal ducks. Supplementing 9% breadfruit leaf powder was effective to lower fat level and meat cholesterol and improve the wellness of male Tegal duck.